Activation of FoxO1/ PGC-1α prevents mitochondrial dysfunction and ameliorates mesangial cell injury in diabetic rats. (15th September 2015) - Wu, Lina; Wang, Qingzhu; Guo, Feng; Zhou, Yingni; Ji, Hongfei; Liu, Fei; Ma, Xiaojun; Zhao, Yanyan; Qin, Guijun
Abstract: The generation of hyperglycemia-induced mitochondrial reactive oxygen species (ROS) is a key event in diabetic nephropathy development. The forkhead-box class O1 (FoxO1) and peroxisome proliferator-activated receptor γ co-activator 1α (PGC-1α) proteins are implicated in oxidative stress. We investigated the in vivo association of FoxO1 and PGC-1α in renal cortices from streptozotocin-induced diabetic rats and in rat kidney mesangial cells (MCs) treated with high glucose, in vitro. High-glucose induced FoxO1 inhibition was associated with decreased PGC-1α expression in MCs. These changes were accompanied by mitochondrial dysfunction and increased ROS generation. However, constitutive FoxO1 activation increased PGC-1α expression and partially reversed these changes, which were significantly decreased by the treatment of PGC-1α-small interfering RNA. We identified PGC-1α as a direct FoxO1 transcriptional target by chromatin immunoprecipitation. In addition, lentiviral-mediated FoxO1 overexpression in diabetic-rat kidneys significantly increased PGC-1α, NRF-1, and Mfn2 expression, and decreased malondialdehyde production and proteinuria. These data suggest that FoxO1/PGC-1α activation protected rats against high-glucose-induced MC injury by attenuating mitochondrial dysfunction and cellular ROS production. Highlights: FoxO1/PGC-1α associations were studied following high-glucose (HG) treatment. HG treatment inhibited FoxO1/PGC-1α expression in rat kidney mesangial cells (MCs). Biochemical changes following FoxO1/PGC-1α downregulation were characterized. PGC-1α was found to be a direct FoxO1 transcriptional target. FoxO1/PGC-1α activation protected against HG-induced MC injury in vivo.